Discursos de la pandemia en la atención gerontológica de los adultos mayores beneficiaros del Centro de Adulto Mayor Trujillo-EsSalud en el período marzo 2020-julio 2021 - Cerdan Chavarri, Jessy Lorena (2023)
This research analyzes the relationship between the health discourses of Covid-19 with the gerontological assistance of the elderly beneficiaries of the Trujillo Senior Citizen Center in the period of March 2020-July to 2021. The design of this research is applied-descriptive since it will be based on collecting information on a particular phenomenon based on the application of descriptive methods of the quantitative and qualitative approaches. Therefore, this research has a mixed approach. The population is the total number of elderly beneficiaries attended by the Trujillo-EsSalud Senior Center from March 2020 to July 2021. Said population was 150 older adults who participated in the virtual modality. 10 interviews were applied to older adults from the Trujillo-EsSalud Senior Citizen Center. It was determined that the speeches were based on creating a sense of vulnerability and creating isolation of security devices. It had an impact on the functioning of the CAM and on the stability of the elderly, which they found in the relationships with the collaborators of the institution and the family as support networks.